Digital Resilience among Early Adolescents: An Exploratory Study of Communication Patterns and Digital Literacy in Social Media - Noor Afy Shovmayanti; Khusnul Amalin (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2026)
The rapid proliferation of social media has fundamentally reshaped how early adolescents engage in communication, identity construction, and social learning. Despite growing scholarly attention to adolescents’ digital practices, limited research has examined how communication patterns within closed messaging platforms, such as WhatsApp, function as mechanisms for developing digital resilience among early adolescents aged 10–13 years. This gap is critical, given their heightened vulnerability to online risks due to still-developing emotional regulation and digital awareness. This study aims to address this gap by examining how digital resilience is shaped through everyday communication practices in a semi-urban context in Klaten, Indonesia. Employing a qualitative exploratory design, data were collected from 26 participants through demographic surveys, in-depth interviews, and digital ethnography. The findings reveal that digital resilience is an emergent, relational process shaped by the interplay of self-regulation, evolving privacy awareness, informal behavioural norms, and sustained external mediation from parents and teachers. Notably, WhatsApp group interactions function as micro-social ecosystems where emotional regulation, empathy, and adaptive communication strategies are negotiated and practised. This study advances the conceptualisation of digital resilience as a communication-driven developmental competence and underscores the importance of dialogic digital parenting and context-sensitive literacy interventions in fostering adaptive digital engagement